2015
DOI: 10.1371/journal.pntd.0004173
|View full text |Cite
|
Sign up to set email alerts
|

Polyanhydride Nanoparticle Delivery Platform Dramatically Enhances Killing of Filarial Worms

Abstract: Filarial diseases represent a significant social and economic burden to over 120 million people worldwide and are caused by endoparasites that require the presence of symbiotic bacteria of the genus Wolbachia for fertility and viability of the host parasite. Targeting Wolbachia for elimination is a therapeutic approach that shows promise in the treatment of onchocerciasis and lymphatic filariasis. Here we demonstrate the use of a biodegradable polyanhydride nanoparticle-based platform for the co-delivery of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 53 publications
3
43
1
Order By: Relevance
“…This may explain why M:(FA-NP) is more efficacious in neuroprotection over Mito-Apo alone. The encapsulation efficiency coupled with the equivalent protection as compared to Mito-Apo alone also indicates that the nano-formulations provide dose-sparing, which has been observed previously (19, 66). …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This may explain why M:(FA-NP) is more efficacious in neuroprotection over Mito-Apo alone. The encapsulation efficiency coupled with the equivalent protection as compared to Mito-Apo alone also indicates that the nano-formulations provide dose-sparing, which has been observed previously (19, 66). …”
Section: Discussionsupporting
confidence: 80%
“…A significant advantage provided by the polyanhydride nanoparticles is the slow and controlled erosion of the particles, enabling a sustained release of the encapsulated cargo (19). The FA functionalization of Mito-Apo-containing nano-formulations lowered the encapsulation efficiency as expected because of exposure to aqueous conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PLGA nanoparticles have been used to encapsulate ivermectin and demonstrated elimination of filarial worm parasites from circulation with dose sparing effects [186]. Recent studies from our laboratories have demonstrated success in using polyanhydride nanoparticles encapsulating anti-filarial drugs and antibiotics to kill parasites with several thousand fold dose-sparing [187]. Imaging of filarial worms incubated in vitro with drug-loaded polyanhydride nanoparticles indicated that these nanoparticles penetrated the worm cuticle and persist, in contrast to soluble drugs [187].…”
Section: Case Studiesmentioning
confidence: 99%
“…Recent studies from our laboratories have demonstrated success in using polyanhydride nanoparticles encapsulating anti-filarial drugs and antibiotics to kill parasites with several thousand fold dose-sparing [187]. Imaging of filarial worms incubated in vitro with drug-loaded polyanhydride nanoparticles indicated that these nanoparticles penetrated the worm cuticle and persist, in contrast to soluble drugs [187]. It has been speculated that encapsulation of drugs into particles may reduce the ability of filarial worms to regulate mechanisms (i.e., changes in glutamate-gated chloride channels or ABC transporter expression) that enable recovery of the worm via the expulsion of soluble drugs [11, 55, 56].…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation